MILLERITE OF THE KAPITANIVSKY ULTRABASITE MASSIF (GOLOVANIVSKA SUTURE ZONE) - Bochevar, R.; Skakun, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this paper the finds of millerite in the Kaitanivsky ultrabasite massif was described. Dimensional placing of mineral in the rock, morphology of grains, chemical composition and mineral associations were determined. The genesis and importance of millerite among sulfide ores of ultrabasite formations of the Kapitanovsky ore field have been proved.